2021
DOI: 10.1038/s41598-021-99511-6
|View full text |Cite
|
Sign up to set email alerts
|

Novel chemical stimulation for geothermal reservoirs by chelating agent driven selective mineral dissolution in fractured rocks

Abstract: Improving geothermal systems through hydraulic stimulation to create highly permeable fractured rocks can induce seismicity. Therefore, the technique must be applied at a moderate intensity; this has led to concerns of insufficient permeability enhancement. Adding chemical stimulation can mitigate these issues, but traditional methods using strong mineral acids have challenges in terms of achieving mineral dissolution over long distances and highly variable fluid chemistry. Here, we demonstrate a novel chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Furthermore, the groundwater in the potential CO 2 storage site usually contains significant amounts of divalent cations, which potentially impedes the leaching of more cations from rocks due to the dissolution/precipitation equilibrium. To overcome these challenges and vary the dissolution/precipitation equilibrium, recent studies, including our previous work, have demonstrated that the incorporation of additives, such as chelating agents, can effectively enhance mineral dissolution by selectively extracting metals. , The utilization of such advanced approaches should also be considered for the advancement of the CO 2 mineralization technology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the groundwater in the potential CO 2 storage site usually contains significant amounts of divalent cations, which potentially impedes the leaching of more cations from rocks due to the dissolution/precipitation equilibrium. To overcome these challenges and vary the dissolution/precipitation equilibrium, recent studies, including our previous work, have demonstrated that the incorporation of additives, such as chelating agents, can effectively enhance mineral dissolution by selectively extracting metals. , The utilization of such advanced approaches should also be considered for the advancement of the CO 2 mineralization technology.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these challenges and vary the dissolution/precipitation equilibrium, recent studies, including our previous work, have demonstrated that the incorporation of additives, such as chelating agents, can effectively enhance mineral dissolution by selectively extracting metals. 44 , 45 The utilization of such advanced approaches should also be considered for the advancement of the CO 2 mineralization technology.…”
Section: Resultsmentioning
confidence: 99%
“…These changes in the hydraulic behavior of a reservoir can also benefit geothermal exploitation, as flow paths inside the fracture network might become altered so that thermal exploitation in previously neglected parts of the reservoir is increased. Clogging and opening of fractures can also be triggered through anthropogenic stimulation techniques 38 , 39 and might provide future optimization techniques for geothermal reservoirs.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the resulting fractures within the CFN have narrow apertures in both conventional and superhot geothermal environments, reducing their potential to provide additional connections for the natural fractures. Therefore, further stimulation, such as a longer pressurization duration (Goto et al 2021) or the use of chemical stimulation to dissolve rock-forming minerals at conventional geothermal temperatures (Watanabe et al 2021b), may improve the permeability of the CFN. Third, the low viscosity of CO 2 may also impose challenges during field-scale operation: CO 2 could flow far within the natural fracture network, especially under conventional geothermal conditions, such that increasing the pressure is difficult.…”
Section: Implications Enhanced Geothermal System Developmentmentioning
confidence: 99%